Faith and Reason in the Thought of St. Augustine - Cushman, Robert Eugene (Church history, 1950)
Christianity boldly asserted that the eternal Logos had been manifested in the personal history of Jesus called Christ. Once this claim began to receive wide acceptance, the older ways of philosophizing characteristic of the classical ages were shaken. On the one hand, Christians affirmed positively that God had drawn nigh, disclosing himself in history to those who believed. On the other hand, they held that, apart from reliance upon this divine disclosure, the efforts of scientific reason to apprehend God were pitifully inadequate and perverse.